The Effect of Idiomatic Translation Method In the Student’s Ability On Translating Descriptive Text - Elisabeth Ruthana Lasmaria Sinaga, M.Pd (JURNAL CURERE, 2019)
This study deals with the effect of Idiomatic Translation Method in students’ translating descriptive text. The objective of the study is to find out whether Idiomatic translation method affects students’ ability in Translate descriptive text. In carrying out this study, the writer took 40 of 2012 academic year students of English department of HKBP NOMMENSEN UNIVERSITY MEDAN and two classes taken as the sample of her study. They were divided into two groups.The first group (20 students) Group C was experimental group, who was taught by using Idiomatic Translation Method on students’ translate descriptive text while the second group (20 students) Group D was the control group, the descriptive text was taught by using Literal Translation Method. The instrument of the test was written test. Those were pre-test and post-test. The scores of the test were taken to be the data and calculated using t-test formula. The result of computing the t-test show that t-observe is bigger than t-table (1.338 <1.685) at the level of 0.05 with the degree of freedom (df) 38, It means that the value of the observed was bigger than value of t-table. It means that the hypothesis “Idiomatic Translation Methodno significantly effect on students’ translating Descriptive text” is Rejected.